Experimental Study of the Positive Ion Feedback from Gas to Liquid in a Dual-Phase Argon Chamber and Measurement of the Ion Mobility in Argon Gas - Luciano Romero; Roberto Santorelli; Edgar Sánchez García; Thorsten Lux; Michael Leyton; Silvestro di Luise; Pablo García Abia; Rodrigo López Manzano; José Manuel Cela-Ruiz; Sebastián Quizhpi; Vicente Pesudo (Universe, 2022)
The dynamics of the positive ions created by particle interactions inside argon time projection chambers plays an important role in characterizing the next generation of massive detectors planned for the direct search for dark matter and the study of neutrino properties. We have constructed a 1 L liquid argon chamber (ARION: ARgon ION experiment) with a high voltage pulse generator capable of injecting, in a controlled manner, a sizeable ion current into the drift region. This chamber is capable of reproducing a volume charge similar to that found in large detectors, allowing its effects to be studied systematically. New experimental results regarding ion dynamics in the liquid and direct demonstration of ion feedback from the gas to the liquid are discussed in this paper. In addition, a novel technique to measure the drift velocity of argon ions is introduced along with preliminary results obtained in gas.